Heroes in crisis: Trauma centers should be screening for and intervening on posttraumatic stress in our emergency responders. Issue 1 (July 2020) - Tatebe, Leah C.; Rajaram Siva, Nandini; Pekarek, Sydney; Liesen, Erik; Wheeler, Andrew; Reese, Carol; Schlanser, Victoria; Kaminsky, Matthew; Messer, Thomas; Starr, Frederic; Mis, Justin; Bokhari, Faran; et al.
Abstract : BACKGROUND: Emergency responders face a crisis of rising suicide rates, and many resist seeking help due to the stigma surrounding mental health. We sought to evaluate the feasibility of an urban trauma center to screen for posttraumatic stress (PTS) among emergency responders and to provide mental health services. METHODS: Paramedics, firefighters, law enforcement, and corrections officers involved with patients in the trauma unit were asked to complete the Post-Traumatic Growth Inventory (PTGI) and Post-Traumatic Checklist for Diagnostic and Statistical Manual-5 (PCL-5). Additional factors known to affect PTS were correlated: occupation, age, sex, years of service, marital status, children, and pets. Willingness and barriers to seeking interventions for PTS were evaluated. RESULTS: A total of 258 responded: 36.7% paramedics, 40.2% law enforcement officers, 18.4% corrections officers, 0.8% firefighters, and 3.5% with multiple positions. Responders had a mean of 14.5 years of service (SD, 9.9 years). Mean PTGI and PCL-5 scores were 52.1 (SD, 25.1) and 17.2 (SD, 16.5), respectively. Overall, 24.7% had diagnostic PTS disorder with no difference seen in rates between professions. Of these, 80.7% had not sought care. Barriers included that they were not concerned (46%), did not recognize symptoms (24%), and were worried about consequences (20%). Concern over career advancement or losing one's job was the greatest barrier cited for seeking care. Among law enforcement, 47.7% were concerned that they would lose their ability to carry a firearm if they sought care for PTS. The PTGI score, divorce, and 46 years to 50 years were the only factors examined that correlated with increased PCL-5 score. There were 82.5% that felt the trauma center was the right place to screen and intervene upon PTS. CONCLUSION: Trauma centers are an ideal and safe place to both screen for PTS and offer mental health assistance. Comprehensive trauma-informed care by hospital-based intervention programs must expand to include emergency responders. LEVEL OF EVIDENCE: Epidemiological study type, Level II. Abstract : Supplemental digital content is available in the text.